The Role of Spirituality in the Lives of Black Same Gender Loving Men at Midlife - Larry Bryant; Lorenzo Bowman (Adult Education Research Conference, 2011)
This paper addresses the role of spirituality in the lives of Black Same Gender Loving (SGL) men. Findings from the analysis of three autoethnographies indicate Black SGL men experience same sex attraction at an early age, reevaluate the religious and spiritual teachings of their youth, attend church at an early age, consider spirituality an integral part of their daily lives, and utilize spirituality in reaching reach out to others.
Keywords: Black gay men; sexuality; sexual orientation; spirituality; same gender loving.